ANALISIS SIKAP ILMIAH PESERTA DIDIK PADA PRAKTIKUM MANDIRI BERBASIS PROYEK PADA MATERI OPTIK SMPN 4 SOJOL DI MASA PANDEMIK - Ardiansyah Ardiansyah; Mu’aminah Mu’aminah (Program Studi Tadris Ilmu Pengetahuan Alam, Fakultas Tarbiyah dan Ilmu Keguruan (FTIK), Institut Agama Islam Negeri (IAIN) Palu, 2020)
The implementation of practicum in science learning in schools has also experienced limitations due to the pandemic, therefore science teachers must innovate to create something breakthrough so that practicum can continue to be carried out to foster scientific attitudes in students. This study aims to analyze the increase in scientific attitudes of students in project-based independent practicum. This research was conducted at SMPN 4 Sojol using a quasi experiment method with one experimental class. Data collection was carried out by pretest, posttest using a scientific attitude questionnaire, at the implementation stage of project-based practicum learning through three stages, namely planning, implementing and evaluating using qualitative data in the form of observation. The results of observations in the planning, implementation and evaluation stages of students' scientific attitudes showed a positive trend. Meanwhile, the implementation of practicum which was carried out independently based on the project showed an increase in the N-Gain value from the scientific attitude questionnaire at the pretest and posttest. The mean value of N-Gain for curiosity was 0.71 or included in the